Yield, water productivity and economic return of deficit-drip-irrigated tomatoes in Kaduna (Nigeria) - Obiajulu Onwuegbunam Donatus; Abubakar Oyebode Muyideen; Evonameh Igbadun Henry; Ismail Habibu (Journal of Agricultural Sciences (Belgrade), 2023)
Compared to gravity flow systems, pressurized drip irrigation provides more efficient control of the amount of water applied, better irrigation uniformity, and a higher initial capital and operation costs. Hence, an economic analysis is required to determine its profitability over a projected time period. Field experiments were conducted in Afaka (Kaduna, Nigeria), during two dry seasons of 2018 and 2019 to determine the effect of regulated deficit irrigation on the yield, crop water productivity, and projected economic returns of UC 82B tomatoes under pressurized drip irrigation. The economic returns were evaluated using the benefit-cost ratio, net present values, and payback period analyses. The highest fresh fruit yield (19.0 t/ha) was obtained in the full irrigation treatment (T1), while the highest crop water productivity (4.94 kg/m3 ) was obtained in the deficit treatment with full irrigation at the vegetative and flowering stages followed by 60% of reference evapotranspiration at maturity (T7). The project was found to be profitable over the projected years, with benefit-cost ratios of 1.90 and 1.69; payback periods of 2.7 and 3.2 years for T1 and T7, respectively. The full irrigation of tomatoes was therefore found to be more economical than deficit irrigation in the area, with water not being considered as a limiting factor in terms of costs. Gravity drip irrigation was recommended to reduce the pumping cost of irrigation and thereby increase the profit margin.